Measuring projectmanagement efficiency by Data Envelopment Analysis - Siposné Sinóros-Szabó, Laura (Acta Agraria Debreceniensis, 2015)
I suppose that there is a relation between the success of EU-funded projects and the effectiveness of project management teams which implement them. To examine the accuracy of the assumption and the nature of the relationship I needed a measurement method that was suitable for measuring the effectiveness of project management teams implementing EU funded projects in a given construction. Since Data Envelopment Analysis (DEA) has already been used to measure the efficiency of decision making units in other areas, it seems suitable for measuring project management effectiveness and indirectly measuring project efficiency.